The role of Generative Artificial Intelligence in the creation of educational resources - Pizones Bejarano, Cecilia (2025)
Generative Artificial Intelligence (GAI) is perceived as a disruptive technology in education. The implementation of this emerging tool is seen as an opportunity for personalizing learning through the creation of resources. The objective of this study is to explore the role that Generative AI plays in the creation of personalized educational resources for students with Specific Educational Support Needs (SESN). To this end, a descriptive and qualitative experimental design was chosen, using semi-structured interviews and participant observations to gather information and identify needs at a psycho-pedagogical center in Seville. Difficulties in reading and writing and emotionalbehavioral difficulties were detected among the center's users, as well as a lack of training in digital skills. In response, two educational materials were designed and implemented using free AI applications, which were implemented in three users of the center with NEAE. The results pointed to the effectiveness and benefits of AI as a viable and effective tool for creating educational materials and personalizing the learning process, improving participation and motivation, and developing key skills.